Limitaciones del sistema de libertad anticipada costarricense: Estudio de caso del sistema japonés para la implementación de reformas penitenciarias. - García Ramírez , Daniel (2024)
This article examines the challenges faced by the Costa Rican early release system as a direct consequence of the lack of a solid regulatory structure.